Proceedings IEEE Workshop on Visual Languages
DOI: 10.1109/wvl.1992.275777
|View full text |Cite
|
Sign up to set email alerts
|

Visual translation: from native language to sign language

Abstract: Visu.al translation is a new and promising research field for practical and academic reasons. A model of a system which translates text from a native language into animated sign language is described in this paper. W e have also described some design principles and applied methodologies which we believe can be guiding principles for later researchs in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The Thalmanns [23,44] improved on the hand model to include much better skin models and deformations of the finger tips and the gripped object. Lee and Kunii [38] built a system that includes handshapes and simple pre-stored facial expressions for American Sign Language (ASL) synthesis. Dynamics of arm gestures in ASL have been studied by Loomis et al [42].…”
Section: Literature On Gesture Animationmentioning
confidence: 99%
“…The Thalmanns [23,44] improved on the hand model to include much better skin models and deformations of the finger tips and the gripped object. Lee and Kunii [38] built a system that includes handshapes and simple pre-stored facial expressions for American Sign Language (ASL) synthesis. Dynamics of arm gestures in ASL have been studied by Loomis et al [42].…”
Section: Literature On Gesture Animationmentioning
confidence: 99%
“…The Thalmanns [18,26] improved on the hand model to include much better skin models and deformations of the finger tips and the gripped object. Lee and Kunii [22] built a system that includes handshapes and simple pre-stored facial expressions for American Sign Language (ASL) synthesis. Dynamics of arm gestures in ASL have been studied by Loomis et al [25].…”
Section: Literature On Gesture Animationmentioning
confidence: 99%
“…Like spoken or written languages, sign languages used in different countries are different and standard. For example, American Sign Language (ASL) is used by approximately one-half million deaf people in the United States and Canada [10]. ASL is one of the most complete sign systems in the world.…”
Section: Thai Sign Languagementioning
confidence: 99%
“…Lee and Kunii [10] suggested that the three classical machine translation including direct, transfer and interlingua can be adapted to be used in sign translation.…”
Section: Introductionmentioning
confidence: 99%